2021
DOI: 10.1029/2020jb020888
|View full text |Cite
|
Sign up to set email alerts
|

Cross Validation of Stress Drop Estimates and Interpretations for the 2011 Prague, OK, Earthquake Sequence Using Multiple Methods

Abstract: Earthquake source parameters provide important insight into the physical source processes occurring during earthquake rupture. The increase in seismicity rate within the central United States related to wastewater disposal from oil and gas production (Langenbruch & Zoback, 2016; Zhai et al., 2019) has led to a number of studies attempting to determine whether the source parameters of these induced earthquakes differ from those of tectonic earthquakes. Such a finding could allow for the identification of induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 77 publications
(232 reference statements)
5
37
0
Order By: Relevance
“…They also concluded that relative parameters were better resolved than absolute values, a finding supported by the comparative analysis of Pennington et al. (2021).…”
Section: Introductionmentioning
confidence: 75%
“…They also concluded that relative parameters were better resolved than absolute values, a finding supported by the comparative analysis of Pennington et al. (2021).…”
Section: Introductionmentioning
confidence: 75%
“…Comparison of different methods (e.g. [15,120,194]) and the use of synthetic tests [98] are all helping to distinguish earthquakes with better and poorer parameters estimates, and detect systematic bias. Analysis of earthquakes recorded by dense nodal arrays is also helping to quantify the inherent uncertainties from more typical numbers of stations [145,195], and methods that do not require assumption of a source model could prove useful (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of events for which one can estimate spectral parameters decreases between the single‐spectrum and CEM approaches, and decreases drastically for spectral‐ratio fitting. The relative merits between comparing the results using different approaches is that it can help identify biases in individual methods while retaining a larger number of events for which parameter estimates can be interpreted (Pennington et al., 2021).…”
Section: Source Parameter Inversion: Spectral Analysismentioning
confidence: 99%